Ringwomb in ewes and does - MAVROGIANNI (Β.Σ. ΜΑΥΡΟΓΙΑΝΝΗ) V. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
In this paper, the literature on ringwomb in sheep and goats is reviewed. In the first part of the article, the endocrinology of normal parturition in small ruminants is reviewed and the literature on myometrial contractions and the stages of labour is briefly presented. Subsequently, factors that have been associated with this condition are mentioned and the pathogenesis of the disorder is discussed. The literature on the significance of ringwomb as a cause of dystocia is reviewed and methods for treatment of the disorder are presented.